PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT ASURANSI UMUM BUMIPUTERA MUDA 1967 - , Rini Rosmiyati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research is to investigate the effects of leadership style, motivation and perceptions of organizational culture to employees performance in PT. Bumiputera Muda 1967 General Insurance. This research use proporsional random sampling method and data that used in this research is primary data of questionnaire with sampling total about 65 respondent who is the employee of PT. Bumiputera Muda 1967 General Insurance. The feasibility of instrument tested through validity and reliability test, meanwhile data analysis used multiple regression method by assistance SPSS v 17 program. This result of this research indicate that: (1) Leadership style in PT. Bumiputera Muda 1967 General Insurance is democratic leadership